2020
DOI: 10.1101/2020.12.18.423527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decidual cell differentiation is evolutionarily derived from fibroblast activation

Abstract: What the molecular mechanisms underlying the evolutionary origin of novel cell types are is a major unresolved question in biology. The uterine decidual cell is a novel cell type of placental mammals which serves as the interface between maternal and fetal tissues during pregnancy. In this paper, we investigate two models for the nature of the differentiation of decidual cells: first, that it represents a mesenchymal-epithelial transition (MET), and second, that it evolved from wound-induced fibroblast activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Extant mammals span several major evolutionary transitions during the origins, divergence, and conservation of pregnancy, including the origin of new cell-types in the uterine lining (endometrium), endometrial stromal fibroblasts (ESFs), and decidual stromal cells (DSCs) ( Erkenbrack et al 2018 ; Wu et al 2020 ; Chavan et al 2021 ), which mediate many of the maternal responses to pregnancy. For example, an essential step in the establishment and maintenance of pregnancy is the differentiation (decidualization) of ESFs into DSCs in response to progesterone acting through the progesterone receptor (PGR), the second messenger cyclic AMP (cAMP) acting through protein kinase A (PKA), the transcription factor FOXO1 ( Gellersen and Brosens 2003 ; Kajihara et al 2013 ), and, in some species, to fetal signals ( Gellersen et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extant mammals span several major evolutionary transitions during the origins, divergence, and conservation of pregnancy, including the origin of new cell-types in the uterine lining (endometrium), endometrial stromal fibroblasts (ESFs), and decidual stromal cells (DSCs) ( Erkenbrack et al 2018 ; Wu et al 2020 ; Chavan et al 2021 ), which mediate many of the maternal responses to pregnancy. For example, an essential step in the establishment and maintenance of pregnancy is the differentiation (decidualization) of ESFs into DSCs in response to progesterone acting through the progesterone receptor (PGR), the second messenger cyclic AMP (cAMP) acting through protein kinase A (PKA), the transcription factor FOXO1 ( Gellersen and Brosens 2003 ; Kajihara et al 2013 ), and, in some species, to fetal signals ( Gellersen et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the process, EVTs interact with the decidual endometrial fibroblasts (dESFs) ( Figure 1A ). We have previously reported that decidualization is evolutionarily derived from fibroblast activation ( Wu et al, 2020 ). Indeed, we had found that differentiation of ESFs involves an interim stage which mimics activation of fibroblasts in response to wounding, which gets extended to a larger program of decidualization ( Wu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that decidualization is evolutionarily derived from fibroblast activation ( Wu et al, 2020 ). Indeed, we had found that differentiation of ESFs involves an interim stage which mimics activation of fibroblasts in response to wounding, which gets extended to a larger program of decidualization ( Wu et al, 2020 ). Early decidualization, therefore, appeared to be mimicking increase in ESF contractility and generation of mechanical forces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant mammals span several major evolutionary transitions during the origins, divergence, and conservation of pregnancy, including the origin of new cell-types in the uterine lining (endometrium), endometrial stromal fibroblasts (ESF), and decidual stromal cells (DSC) (Chavan et al, 2021; Erkenbrack et al, 2018; Wu et al, 2020), which mediate many of the maternal responses to pregnancy. For example, an essential step in the establishment and maintenance of pregnancy is the differentiation (decidualization) of ESFs into DSCs in response to progesterone acting through the progesterone receptor (PGR), the second messenger cyclic AMP (cAMP) acting through protein kinase A (PKA), the transcription factor FOXO1 (Gellersen and Brosens, 2003; Kajihara et al, 2013), and, in some species, to fetal signals (Gellersen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%